2016
DOI: 10.1002/adhm.201600211
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Silk as a Scaffold for Mature, Sustainable Unilocular Adipose 3D Tissue Engineered Systems

Abstract: There is a critical need for monitoring physiologically relevant, sustainable, human adipose tissues in vitro to gain new insights into metabolic diseases. To support long term culture, a 3D silk scaffold assisted culture system was developed that maintained mature unilocular adipocytes ex vivo in co-culture with pre-adipocytes, endothelial cells, and smooth muscle cells obtained from small volumes of liquefied adipose samples. Without the silk scaffold, adipose tissue explants could not be sustained in long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 96 publications
3
86
0
Order By: Relevance
“…It has been used to image the large unilocular lipid droplet of mature adipocytes (Le et al, 2007), which is the hallmark of their in vivo phenotype. In prior work (Abbott, Wang, et al, 2016), we found that our adipose tissue system maintained unilocular mature adipocytes with destructive imaging techniques. To validate that this phenotype could be detected with non-destructive methods, we used CARS imaging in the current study demonstrating that there was not a significant effect of time in culture on the unilocular lipid areas of adipocytes ( Figure 1b).…”
Section: Non-destructive Tracking Indicates That Cells Maintain Thementioning
confidence: 73%
See 4 more Smart Citations
“…It has been used to image the large unilocular lipid droplet of mature adipocytes (Le et al, 2007), which is the hallmark of their in vivo phenotype. In prior work (Abbott, Wang, et al, 2016), we found that our adipose tissue system maintained unilocular mature adipocytes with destructive imaging techniques. To validate that this phenotype could be detected with non-destructive methods, we used CARS imaging in the current study demonstrating that there was not a significant effect of time in culture on the unilocular lipid areas of adipocytes ( Figure 1b).…”
Section: Non-destructive Tracking Indicates That Cells Maintain Thementioning
confidence: 73%
“…Although there is a consistent ratio between the number of adipose tissue stromal cells and adipocytes (unrelated to BMI), during adipose expansion, cell size precedes the increase in fat cell number (van Harmelen et al, 2003); therefore, normalizing by DNA content in the current study may have added an additional confounding factor. Furthermore, different populations of cells may proliferate more than others (i.e., fibroblasts over adipocytes), although our prior work (Abbott, Wang, et al, 2016) demonstrates that these cell types are present throughout culture. These factors likely contributed to the large variation in lipolytic responses and glucose uptake observed in the current study.…”
Section: Patient-specific Differences In Response To Tnfα Stimulationmentioning
confidence: 98%
See 3 more Smart Citations